-10(3a-6)=-3a-11(6a-9)

Simple and best practice solution for -10(3a-6)=-3a-11(6a-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(3a-6)=-3a-11(6a-9) equation:


Simplifying
-10(3a + -6) = -3a + -11(6a + -9)

Reorder the terms:
-10(-6 + 3a) = -3a + -11(6a + -9)
(-6 * -10 + 3a * -10) = -3a + -11(6a + -9)
(60 + -30a) = -3a + -11(6a + -9)

Reorder the terms:
60 + -30a = -3a + -11(-9 + 6a)
60 + -30a = -3a + (-9 * -11 + 6a * -11)
60 + -30a = -3a + (99 + -66a)

Reorder the terms:
60 + -30a = 99 + -3a + -66a

Combine like terms: -3a + -66a = -69a
60 + -30a = 99 + -69a

Solving
60 + -30a = 99 + -69a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '69a' to each side of the equation.
60 + -30a + 69a = 99 + -69a + 69a

Combine like terms: -30a + 69a = 39a
60 + 39a = 99 + -69a + 69a

Combine like terms: -69a + 69a = 0
60 + 39a = 99 + 0
60 + 39a = 99

Add '-60' to each side of the equation.
60 + -60 + 39a = 99 + -60

Combine like terms: 60 + -60 = 0
0 + 39a = 99 + -60
39a = 99 + -60

Combine like terms: 99 + -60 = 39
39a = 39

Divide each side by '39'.
a = 1

Simplifying
a = 1

See similar equations:

| -3/2(r+3)=15 | | -11=c+7 | | -11n=-1 | | 0.3x+8.2=4.4x | | x-0.55x= | | 8k-32=10k-(1+2k) | | 2x^3+5x^2+3=0 | | -17=9w | | 1+1=4 | | -30-7x=-5(6-8x) | | (x^2+x)(2x+5)+3=x(2x+5) | | 37=36+x | | 3y+y=20 | | 8x+26=-2(x+7) | | -6a=-18 | | 6x(2x-1)=3-1 | | -20=-3a | | x^3(6x+24)=0 | | 2(-6v+6)=108 | | 3x+8=83 | | -4+5(-6+5b)=-134 | | -2r=20 | | 4x^2-35+24=0 | | 2p/3-15=-19 | | 2x=12x-18 | | 6(2x-5)=-(x-4) | | 5(x+2)+x=29 | | 0=12-17x+6x^2 | | X(2x-5)=-(x-4) | | (9+m)/3=2 | | 5+2(x+7)=20 | | -9+(n/4)=-7 |

Equations solver categories